IMPLEMENTATION OF MICROCONTROLLER AS A VEHICULAR AD-HOC NETWORK (VANET) BASED VEHICLE COMMUNICATION TOOL TO MEASURE AIR POLLUTION - Abduh, Ibrahim; Yahya, Muhammad; Mappalotteng, Abdul Muis; Purnamawati, Purnamawati (Pascasarjana Universitas Negeri Makassar, 2025)
This research examines the impact of air pollution on human health which can cause various serious diseases such as cardiovascular diseases, heart attacks, asthma and stroke. According to the World Health Organization (WHO), air pollution causes 7 million deaths every year, due to harmful substances released by air pollution sources. The focus of this research is to design tools that can communicate with each other to measure air quality on Bumi Tamalanrea Permai road, Makassar City using a vehicle network (VANET) and sensors installed on the vehicle. These sensors move and collect data periodically, and the collected data is sent to a base station as a collection center. The research results show that the device developed succeeded in recording sensor-based data well, thus producing important information regarding air quality on Bumi Tamalanrea Permai road. This device is also capable of operating effectively within a VANET network, enabling communication between nodes with a minimum delay of less than 40 meters and a signal strength of less than -77dBm. Communication with the base station uses the MQTT protocol, with low packet loss and data throughput at distances of less than 70 meters and signal strength below -77dBm.